2022
DOI: 10.1093/europace/euab321
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sodium-glucose co-transporter inhibitors on cardiac autonomic function and mortality: no time to die

Abstract: Sodium-glucose co-transporter 2 (SGLT2) inhibitors have been shown to improve cardiovascular outcomes not only in patients with diabetes but also in those with heart failure, irrespective of diabetic status. However, the mechanisms underlying the cardioprotective effects of these newer anti-diabetic drugs remain to be fully elucidated. One exciting avenue that has been recently explored in both preclinical and clinical studies is the modulation of the cardiovascular autonomic nervous system. A reduction in sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Both sodium–glucose transporter-2 (SGLT-2) and angiotensin-converting enzyme (ACE) inhibitors promote preventive and therapeutic effects in attenuating diabetic cardiac dysautonomia [ 25 , 46 , 47 , 48 , 49 , 50 , 51 ]. Despite the lack of SGLT-2 in the heart, studies with gliflozins demonstrated a significant reduction in cardiovascular risk and deaths consequent of DM, which could result in part from the regulation of the autonomic nervous system through the inhibition of renal reabsorption of glucose [ 47 , 50 , 52 ]. Recently, the EMBODY trial indicated that medium-term (6 months) use of empagliflozin (10 mg p.o.…”
Section: Alternative Treatment Of Dm-cardiac Autonomic Neuropathymentioning
confidence: 99%
“…Both sodium–glucose transporter-2 (SGLT-2) and angiotensin-converting enzyme (ACE) inhibitors promote preventive and therapeutic effects in attenuating diabetic cardiac dysautonomia [ 25 , 46 , 47 , 48 , 49 , 50 , 51 ]. Despite the lack of SGLT-2 in the heart, studies with gliflozins demonstrated a significant reduction in cardiovascular risk and deaths consequent of DM, which could result in part from the regulation of the autonomic nervous system through the inhibition of renal reabsorption of glucose [ 47 , 50 , 52 ]. Recently, the EMBODY trial indicated that medium-term (6 months) use of empagliflozin (10 mg p.o.…”
Section: Alternative Treatment Of Dm-cardiac Autonomic Neuropathymentioning
confidence: 99%
“…SGLT2 inhibitors may reduce sympathetic nervous activity but if this is the explanation, a similar reduction in heart rate might have been expected among patients in with sinus rhythm. 16 Alternatively, more patients may have reverted to sinus rhythm in the dapagliflozin group, compared with the placebo group given that an antiarrhythmic and beneficial effect on AF has been suggested for SGLT2 inhibitors. 28,29 Unfortunately, we did not have follow-up ECGs to confirm or refute this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…We also examined the effect of dapagliflozin on heart rate and the effect of dapagliflozin according to heart rate across the spectrum of LVEF because there is some mainly experimental, evidence that SGLT2 (sodium-glucose cotransporter-2) inhibitors reduce cardiac sympathetic nerve activity and increase parasympathetic nervous system activity. 16,17 METHODS Data underlying the findings described in this article may be obtained following AstraZeneca's data-sharing policy described at https://astrazenecagrouptrials.pharmacm.com/ ST/Submission/Disclosure.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, this is probably opposed by the decreased sympathetic activity that results from treatment with gliflozins. A very thorough review on this topic has recently been published [ 144 ]. A review of reports to the Food and Drug Administration adverse event-reporting system revealed fewer atrial fibrillation events in patients on SGLT2 inhibitors compared to other antidiabetic drugs [ 145 ].…”
Section: Adverse Effectsmentioning
confidence: 99%